THE IMPACT OF E-COMMERCE IMPLEMENTATION ON THE INCOME OF SUKMAJAYA'S MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) AFTER THE PANDEMIC PERIOD - Rahmawati Ulfah (Klabat Journal of Management, 2023)
This research is to determine the influence of e-commerce implementation on the income of micro, small, and medium enterprises (MSMEs) in Sukmajaya after the pandemic period and to assess the extent of this influence. The sample size for this research consists of 100 respondents. The data used in this study are primary data collected through questionnaires, and the correlation analysis model adopted is the Pearson Product Moment Correlation. Based on the results of the analysis conducted, a significance level of 5% yields a value of 0.380, which is greater than 0.361. This implies that H0 is rejected, and Ha is accepted, signifying the influence of e-commerce implementation on the income of micro, small, and medium enterprises (MSMEs) in Sukmajaya after the pandemic period. Keywords: E-Commerce, Earning, MSMES, Pandemic